A parametrized variational principle of nonlinear piezoelectricity - He, Ji-Huan (Computer Assisted Methods in Engineering and Science, 2003)
The variational theory is the theoretical basis of the finite element method, meshfree particle methods and other modern numerical techniques. The present paper establishes a family of variational principles for nonlinear piezoelectricity. A new constitutive relation is suggested, which is deduced as a stationary condition of a generalized variational principle.